2016
DOI: 10.1007/s00601-016-1146-5
|View full text |Cite
|
Sign up to set email alerts
|

Hard Exclusive Pion Leptoproduction

Abstract: In this talk it is reported on an analysis of hard exclusive leptoproduction of pions within the handbag approach. It is argued that recent measurements of this process performed by HERMES and CLAS clearly indicate the occurrence of strong contributions from transversely polarized photons. Within the handbag approach such γ * T → π transitions are described by the transversity GPDs accompanied by twist-3 pion wave functions. It is shown that the handbag approach leads to results on cross sections and single-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Additionally, and perhaps more importantly, the double spin asymmetry measurements provide an independent test of the existing GPDs models probing the underlying assumption of H T and ĒT dominance. The first approach to combine A const LL term with σ 0 and σ T T previously measured by CLAS was conducted in [24]. The constant term was calculated within GK model framework using the H T and ĒT convolutions extracted from unpolarized cross section measurements [11,12] and compared to the measurements presented in this work.…”
mentioning
confidence: 99%
“…Additionally, and perhaps more importantly, the double spin asymmetry measurements provide an independent test of the existing GPDs models probing the underlying assumption of H T and ĒT dominance. The first approach to combine A const LL term with σ 0 and σ T T previously measured by CLAS was conducted in [24]. The constant term was calculated within GK model framework using the H T and ĒT convolutions extracted from unpolarized cross section measurements [11,12] and compared to the measurements presented in this work.…”
mentioning
confidence: 99%
“…Under the Colinear Factorization (CF) regime, a parton is emitted from the nucleon, interacts with the incoming virtual-photon, then returns to the nucleon after the interaction [42]. Studies [50,51] have shown that perturbative calculation methods can be used to calculate the scattering process and extract GPDs from data, while preserving the universal description of the hadronic structure in terms of QCD principles. One limitation is that GPD factorization requires t ∼ t min , namely, the process defaults to a fast-meson and slownucleon final state.…”
Section: From Gpds To Tdasmentioning
confidence: 99%
“…Studies [31,32] have shown that perturbation calculation methods can be used As introduced previously, the GPDs depend on x, ξ and t. The ω production process through GPDs in the forward-angle (t-channel) and through TDAs in the backward-angle (u-channel) are schematically shown in Figs. 2.9 (a) and (b), respectively.…”
Section: Gpd and Tdamentioning
confidence: 99%
“…The TDA specifically describes the reaction of backward-angle meson production [30], while GPDs are being actively studied through forward-angle meson production [31,32].…”
Section: U-channel Physics Overviewmentioning
confidence: 99%